Pengaruh Promosi Dan Brand Image Terhadap Keputusan Pembelian Produk Nikki Jaya Roti - Sigma Wulandari; Semuel Batlajery; Fenty Yoseph Manuhutu (Musamus Journal of Business & Management, 2023)
This study aims to determine the effect of promotion and brand image on product purchasing decisions Nikki jaya rot.the population in this research is all costumers at Nikki jaya roti.Breand wich numbered 1201 people the sample of this researchis 92 person.The sampling product used in this study is non propolity with purposive sampling .technigue app roach version 26. The research used is a quantitative approach and using multiple linear regression analysis with SPSS toots from the result of multiple linear regression analysis that has bean processed isobtained eguation Y = 2.11 + 0.421 X1 + 0.727 X2 + e.from the fest results the hypothesis,namely uji t and uji f shows that the promation variable and brand image has influence and is significant partially or product purchase decisions at Nikki jaya roti metter this is evidenced by the thumy promation value of 5.766 < ttabel of 1.986 .with a signiticant level signifikan 0.000 < 0.05.That is accepted,Ho is rejected brand image thitung Brand Image(X2) nilai 20.891 > nilai ttabel 1.986 with level significant 0,000 < 0,05 .that Ha is accepted and Ho is rejected .then Fhitung (511,43) > value Ftabel (3,10) with a significance level of 0,000 < 0,05 so that Ha is accepted HO is rejected the R-Square value 0.929 or 92.9% means that the purchase decision is ex plained by promotion and brand varables image contributes to purchasing decisions by 92.9% with the rema 7.8 % influced by other variabels that are not examined in this study .